2017
DOI: 10.1155/2017/2714095
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble ST2 and Diastolic Dysfunction in Hypertensive Patients

Abstract: Background Echocardiographic evaluation of left ventricular (LV) structural and functional alterations in hypertension has some limitations, potentially overcome by using biomarkers. ST2, a prognostic biomarker for heart failure and myocardial infarction patients, was less studied in hypertension. Aim To analyze the relationship between serum ST2 levels and diastolic dysfunction (DD) in hypertension. Method We enrolled 88 hypertensive outpatients (average age 65 years, 69.3% females) in a prospective study, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
1
24
0
1
Order By: Relevance
“…Atherosclerosis is currently recognized as an inflammatory disorder [5,6] low-grade inflammation being involved in all stages of atherosclerosis . In recent years, inflammation markers have been recognized as risk factors for cardiovascular disease (CVD) [7][8][9] There are still many unknown facts regarding inflammation in MetS.…”
mentioning
confidence: 99%
“…Atherosclerosis is currently recognized as an inflammatory disorder [5,6] low-grade inflammation being involved in all stages of atherosclerosis . In recent years, inflammation markers have been recognized as risk factors for cardiovascular disease (CVD) [7][8][9] There are still many unknown facts regarding inflammation in MetS.…”
mentioning
confidence: 99%
“…Our group (Farcas et al) has previously shown that sST2 could be useful as an early diagnostic biomarker for cardiac remodeling and altered diastolic performance in HBP, providing additional data to echocardiography. It could represent a milestone in early detection of cardiac performance alteration [18]. Furthermore, Wang et al performed a larger study on 344 patients with HBP and HFpEF and showed that sST2 measurement provides diagnostic aid of stable HFpEF, correlated with NYHA class and LVDD [19].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the circulating level of sST2measured at discharge may improve risk stratification scores based on clinical criteria, SYNTAX score, and other biomarker models [28][29][30] . Previously, an elevated level of sST2 was reported as an independent predictor for survival in patients 2869 with several phenotypes of HF (HFrEF, HFmrEF, HF-pEF), as well as for individuals with STEMI/non-STEMI after PCI and thrombolysis, stable coronary artery diseases, atrial fibrillation, diabetes mellitus [31][32][33][34] . Although there is a wide spectrum of predictive biomarkers in STEMI patients undergoing PCI, sST2 appeared to be superior to NT-proBNP, cardiac troponins, myoglobin, CK-MB and clinical findings in prognostication of early STEMI complications and one-year major adverse cardiovascular and cerebrovascular events, defined as a composite of cardiovascular death, non-fatal myocardial infarction, non-fatal stroke, and ischemia-driven revascularization 35,36 .…”
Section: Discussionmentioning
confidence: 99%